From Acceptance to "Othering”: An Analysis of Swedish Changing Identity towards the Refugees and Muslim Minority Groups - Dharmaputra, Radityo; Felayati, Reza Akbar; Suhito, Yohanes Putra (Global Strategis, 2019)
By using the case study of Sweden and the momentum of the refugee crisis in Europe, this research attempts to analyse the extent to which the shifting practice of Swedish policy towards the refugees (as signified by the new 2016 law prohibiting/restricting the entrance of refugees) might prompt some forms of core identity changes related to immigrant and minority groups. Using the poststructuralism as the central perspective on identity, we argue that the flow of refugee during the crisis in 2015-2016 could be classified as an external shock which then compelled a changing practice of Swedish refugee policy. We then try to show the relationship between changing practice and changing identity discourse by tracing the dynamics of the attitude and perception from both the Swedish government and society regarding the refugees and the Muslim minority groups in Sweden. By analysing the main texts in Swedish identity discourses and the media/public discourses, we found that the changing policy reconstitutes (albeit slowly) the identity of Sweden in "othering” the refugees and Muslim minority groups. This kind of "Self/Other” relationship was different from the condition before and during the early days of the refugee crisis. Keywords: the European refugee crisis, Sweden, Muslim Minority Groups, Post-Structuralism, Changing Practices/Discourses. Dengan menggunakan studi kasus Swedia dan momentum krisis pengungsi di Eropa, penelitian ini berupaya menganalisis sejauh mana praktik pergeseran kebijakan Swedia terhadap para pengungsi (sebagaimana ditandai oleh undang-undang baru tahun 2016 yang melarang atau membatasi pintu masuk bagi pengungsi) mungkin mendorong beberapa bentuk perubahan identitas inti yang terkait dengan kelompok imigran dan minoritas. Dengan menggunakan poststrukturalisme sebagai perspektif utama tentang identitas, penulis berpendapat bahwa masuknya pengungsi selama krisis pada tahun 2015-2016 dapat diklasifikasikan sebagai guncangan eksternal yang kemudian mendorong perubahan kebijakan kebijakan pengungsi Swedia. Kami kemudian mencoba menunjukkan hubungan antara praktik yang berubah dan perubahan diskursus identitas dengan menelusuri dinamika tingkah laku dan persepsi dari pemerintah Swedia dan masyarakat terhadap pengungsi dan kelompok minoritas Muslim di Swedia. Dengan menganalisis teks-teks utama dalam diskursus identitas Swedia dan diskursus media atau publik, penulis menemukan bahwa kebijakan yang berubah merekonstruksi (walaupun perlahan-lahan) identitas Swedia dalam "othering" para pengungsi dan kelompok minoritas Muslim. Hubungan "self/other” semacam ini berbeda dengan kondisi sebelum dan selama masa-masa awal krisis pengungsi. Kata-kata kunci: Krisis pengungsi Eropa, Swedia, Kelompok Minoritas Muslim, Post-structuralism, perubahan praktik/diskursus.